2019
DOI: 10.3233/jad-190142
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Associations of Cognitive Function with Perceptions of Pain in Older Adults

Abstract: Background: Sex differences in pain have been shown to exist in older adults with normal cognition and people with Alzheimer’s disease. It is unknown if sex differences in pain in older adults exist in a range of communicative older adults with varying cognitive ability from no impairment to moderately severe cognitive impairment. Objective: This study proposes to compare the association between psychophysical responses to experimental thermal pain between males and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Our data revealed gender differences in the MMSE, with higher means for men. These data are consistent with previous studies on older people without severe cognitive impairment [ 55 , 56 ]. However, women tend to perform less well than men in cognitive functioning at the onset of aging but then stabilize [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our data revealed gender differences in the MMSE, with higher means for men. These data are consistent with previous studies on older people without severe cognitive impairment [ 55 , 56 ]. However, women tend to perform less well than men in cognitive functioning at the onset of aging but then stabilize [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Strikingly, the same study demonstrated that older males had an increased pain tolerance when compared with older females ( Gallant and Hadjistavropoulos, 2017 ). The sex differences relating to pain perception in older persons have also demonstrated by Romano et al (2019) . The authors reported that females have significantly less unpleasantness with moderate pain perception (contact to heat), when compared with males.…”
Section: Pain Transmission and Experience In The Geriatric Populationmentioning
confidence: 90%
“…In the third study, the authors aimed to examine sex differences in response to psychophysical assessment across the cognitive spectrum, including both cognitively intact controls and participants with MCI and AD in each group (Romano et al., 2019 ). The authors excluded participants with MMSE scores below 10 to account for the potential confound of adults with more severe AD since the parent study included communicative adults with AD who scored less than 10 on the MMSE.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies offer significant insight into different aspects of pain perception in AD (Cowan et al., 2017 ; Monroe et al., 2016 ; Romano et al., 2019 ). The first study, Monroe et al., 2016 , is the parent study from which two additional sub‐analyses were conducted.…”
Section: Methodsmentioning
confidence: 99%